Somalia : Second and Final Review Under the Staff Monitored Program and Request for a New Staff Monitored Program-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
Recent developments are broadly favorable and policies are aligned with staff recommendations and program priorities. Reflecting the favorable rainy season, economic activities are recovering from the 2016-17 drought and inflation is easing. The authorities remain strongly committed to policy implementation under the second Staff-Monitored Program (SMP II) which expired in April 2018, and have requested a follow-up 12-month SMP.